The Effectiveness of Technology to Strengthen the Science of Reading Among Second-Semester English Students Culture and Language Languages Faculty, Widya Dharma University Pontianak. - Udur Delima Sibatuara; Vitha Ama Matuate (BLESS, 2026)
This study aims to evaluate the effectiveness of integrating AI-based phonetic software and gamified learning platforms in reinforcing the Science of Reading (SoR) framework among English majors. Employing a quantitative quasi-experimental design with a Nonequivalent Control Group approach, the study involved 70 even-semester students at the Faculty of Languages, Universitas Widya Dharma, Pontianak. Participants were evenly divided into an experimental group (n=35) receiving technology-enhanced instruction using SpeechACE and Quizizz, and a control group (n=35) receiving conventional instruction. Data were collected through pre- and post-tests, observation sheets, and the Technology-Mediated Self-Efficacy Scale (TMSES) over an eight-week intervention. The results indicated that the experimental group achieved a mean gain of 22.17 points, significantly outperforming the control group's 9.35-point gain. An independent t-test confirmed the significance of this difference (t = 8.45, p < .001) with a large effect size (Cohen’s d = 0.92). Qualitative findings revealed that the technological intervention increased class engagement from 60% to 85%, while reducing anxiety and enhancing self-efficacy through instant, private digital feedback. In conclusion, technology-mediated instruction serves as a transformative pedagogical tool that effectively bridges L1 interference, visualizes abstract phonemic concepts, and aligns with the cognitive preferences of digital natives. This study recommends the formal integration of Computer-Assisted Language Learning (CALL) modules into the faculty's curriculum, expanded institutional infrastructure support, and longitudinal research to assess long-term impacts. Key words: Science of Reading, Artificial Intelligence, Computer-Assisted Language Learning (CALL), Gamification, Self-Efficacy.